Invasive Blood Pressure Measurement and In-hospital Mortality in Critically Ill Patients With Hypertension - Zhou, Bin; Lin, Liang-Ying; Liu, Xiao-Ai; Ling, Ye-Sheng; Zhang, Yuan-Yuan; Luo, An-Qi; Wu, Meng-Chun; Guo, Ruo-Mi; Chen, Hua-Li; Guo, Qi (Frontiers in Cardiovascular Medicine, 2021)
Background: Invasive blood pressure (IBP) measurement is common in the intensive care unit, although its association with in-hospital mortality in critically ill patients with hypertension is poorly understood. Methods and Results: A total of 11732 critically ill patients with hypertension from the eICU-Collaborative Research Database (eICU-CRD) were enrolled. Patients were divided into 2 groups according to whether they received IBP. The primary outcome in this study was in-hospital mortality. Propensity score matching (PSM) and inverse probability of treatment weighing (IPTW) models were used to balance the confounding covariates. Multivariable logistic regression was used to evaluate the association between IBP measurement and hospital mortality. The IBP group had a higher in-hospital mortality rate than the no IBP group in the primary cohort (238 (8.7%) vs. 581 (6.5%), p < 0.001). In the PSM cohort, the IBP group had a lower in-hospital mortality rate than the no IBP group (187 (8.0%) vs. 241 (10.3%), p = 0.006). IBP measurement was associated with lower in-hospital mortality in the PSM cohort (odds ratio, 0.73, 95% confidence interval, 0.59-0.92) and in the IPTW cohort (odds ratio, 0.81, 95% confidence interval, 0.67-0.99). Sensitivity analyses showed similar results in the subgroups with high body mass index and no sepsis. Conclusions: In conclusion, IBP measurement was associated with lower in-hospital mortality in critically ill patients with hypertension, highlighting the importance of IBP measurement in the intensive care unit.